Effect of estrous type of teaser female on caprine sexual behavior a nd semen parameters - Oliveira, M. A. L. (Medicina Veterinária, 2014)
The objective was to address if different estrous types of teaser females affect sexual behavior and seminal parameters of Boer bucks under semen collection conditions. Six adult Boer bucks were submitted to 15-day semen collection sessions during a 60 day period. In the first session, the bucks were exposed to a female under natural estrous and subsequently, in the second session, to an estrous-induced teaser female. The reaction time and the quality of the libido were recorded. The total sperm concentration of the ejaculate was positively correlated with the volume, motility and percentage of live sperm when the female with natural estrous was used. In conclusion, the use of teaser female with hormonally induced estrous negatively affects the sexual behavior and semen quality of Boer bucks under semen collection conditions.